Educación formal: ¿rompiendo o perpetuando mitos? - Vivian Carvajal-Jiménez (Revista Electrónica Educare)
Explanation of the historical and social conditions that have led formal education to far from dispelling the myths and stereotypes on the treatment of gender issues and female position perpetuate these situations and legitimate certain practices through the use of biased textbooks, teaching materials and curriculum practices.